Cynophobic Fear Adaptively Extends Peri-Personal Space - Taffou, Marine; Viaud-Delmon, Isabelle (Frontiers in Psychiatry, 2014)
Peri-personal space (PPS) is defined as the space immediately surrounding our bodies, which is critical in the adaptation of our social behavior. As a space of interaction with the external world, PPS is involved in the control of motor action as well as in the protection of the body. The boundaries of this PPS are known to be flexible but so far, little is known about how PPS boundaries are influenced by unreasonable fear. We hypothesized that unreasonable fear extends the neural representation of the multisensory space immediately surrounding the body in the presence of a feared object, with the aim of expanding the space of protection around the body. To test this hypothesis, we explored the impact of unreasonable fear on the size of PPS in two groups of non-clinical participants: dog-fearful and non-fearful participants. The sensitivity to cynophobia was assessed with a questionnaire. We measured participants’ PPS extent in the presence of threatening (dog growling) and non-threatening (sheep bleating) auditory stimuli. The sound stimuli were processed through binaural rendering so that the virtual sound sources were looming towards participants from their rear hemi-field. We found that, when in the presence of the auditory dog stimulus, the PPS of dog-fearful participants is larger than that of non-fearful participants. Our results demonstrate that PPS size is adaptively modulated by cynophobia and suggest that anxiety tailors PPS boundaries when exposed to fear-relevant features. Anxiety, with the exception of social phobia, has rarely been studied as a disorder of social interaction. These findings could help develop new treatment strategies for anxious disorders, by involving the link between space and interpersonal interaction in the approach of the disorder.